PENGELOLAAN MEDIA CERTA ANAK DALAM PEMBENTUKAN BUDI PEKERTI PESERTA DIDIK DI SEKOLAH DASAR - Sutarman, Adang (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2017)
Children's short stories are generally made by adults, contains a number of mandates that can be used as a tool of cultivation of character in students in primary schools. The intrinsic and extrinsic elements in the children's short story selected as teaching materials can be utilized as a medium of character teaching to the students in the elementary school. The best children's short story for children is a short story that gives children a place to look at their lives so as to broaden their insights and knowledge about the lives they live. Such short stories of children are included in the category of short stories that contain pedagogical values. Through the appearance of the characters, the children are enabled to identify the character and make the guidelines for behavior. Therefore, so that children are not wrong in identifying the characters in a story, it takes guidance and guidance from parents when at home and teachers when they are at school. However, sometimes teachers often find it difficult to choose a good child story. In choosing and presenting reading or stories for children, teachers must be selective. Teachers should be able to distinguish reading or a good story and worth reading or not by children. Keywords. Short Stories of Children, Teaching Materials, Manners.